INTERLINGUAL GRAMMATICAL INTERFERENCE IN TEACHING RUSSIAN TO NATIV E SERBIAN LANGUAGE: THE EXAMPLES OF GYMNASIUM “SVETI SAVA” AND 13th BELGRADE GYMNASIUM (Živi jezici: Journal for Foreign Languages and Literatures, 2018)
The aim of our research was to examine interlingual interference in the adoption of different grammatical forms of the Russian language, which are already defined as "weak points" for Serbian speakers. Namely, grammatical interference between these two languages ​​is a frequent occurrence and often represents an obstacle in the acquisition of Russian by speakers whose mother tongue is Serbian. With this in mind, we made a test, in which we included exactly those forms in which the respondent can easily make a mistake, because the same form of the Serbian language will "pull" him to make a mistake, motivated by the form of the mother tongue. After analyzing the tests, we concluded that our hypotheses are correct, that is, that knowledge of certain grammatical forms of the Serbian language makes it difficult to adopt the same form in the Russian language. Since the assumptions were confirmed, we offered several solutions to the given problem.
Keywords: interlingual grammatical interference; second foreign language; examination; the principle of one difficulty; morphology; syntax; gymnasium